Pengaruh Ekuitas Merek dan Kepercayaan Merek terhadap Kepuasaan Pelanggan dan Terhadap Minat Beli Ulang (Studi Pada Wanita Pengguna Skincare dan Bodycare Scarlatte Whitening) - Nabila, Alistiya Najla; Sutedjo, Bambang (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to explain the influence of Brand Equity and Brand Trust on Customer Satisfaction and Repurchase Intentions on Scarlatte Whitening Skincare and Bodycare consumers. This research uses a quantitative type of research. The population used in this research is female employees or employees who use Scarlatte Whitening Skincare and Bodycare products, 94 female employees were used as samples in this research. Data collection for this research used questionnaires written directly on paper and via Google forms sent directly. Data analysis in this research uses Instrument Testing, Model Testing, and Hypothesis Testing based on SPSS data processing. The findings in this research are (1) Customer Satisfaction has a positive and significant effect on Repurchase Intentions. (2) Brand Equity has a positive and significant effect on Customer Satisfaction. (3) Brand Trust has a positive and significant effect on Customer Satisfaction.